Phase transitions and microstructural characterization of martensite in copper based shape memory alloys - Adiguzel, O. (Ios Press, 2014)
Shape memory effect is a peculiar property exhibited by certain alloy system, and shape memory behaviour is evaluated by the structural changes in microscopic scale. Shape-memory effect is based on martensitic transformation, which occurs on cooling from high-temperature parent phase region with the cooperative movements of atoms on {110}-type close-packet planes of parent austenite phase by means of shear-like mechanism. The material changes its internal crystalline structure with martensitic transition, and the ordered structure or super lattice structure is essential for the shape memory quality of the material. Copper based alloys exhibit this property in metastable beta-phase field which has bcc-based high symmetric structure at high temperature parent state. These structures turn into non-conventional stacking ordered structure with low symmetry following two ordered reactions on cooling from high temperatures
1st International Conference on Construction Materials and Structures -- NOV 24-26, 2014 -- Johannesburg, SOUTH AFRICA
Keywords: Martensitic transition; shape memory effect; twinning; detwinning; inhomogeneous shear; Bain distortion; layered structures